Comparative morphological analysis of raw material of Scabiosa isetensisand S. ochroleuca - Zhunussova, M.A.; Ishmuratova М.Yu.; Abdullabekova, R.A.; Zhuravel, I.A. (Fundamental and Experimental Biology, 2018)
Results of the morphological analysis of Scabiosa ochroleuca and Scabiosa isetensisraw materials are given in article. The following diagnostic signs of raw materials of both species are marked out: for a stalk — extent of branching and structure of a surface, extent of omission, color of stalks; for leaves — a form and the size of a sheet plate, section degree, degree of expressiveness of the main vein, color and omission; for inflorescences — a form and the size of an inflorescence; for leaflets of a wrapper — a form, color and degree of an omission; for a flower — a form and the size of a flower, color of a nimbus, length of a spathe and degree of omission.